2014
DOI: 10.3844/ajptsp.2014.114.124
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON GASTROINTESTINAL EFFECTS OF <i>DESMODIUM VELUTINUM</i>: A TRADITIONAL REMEDY FOR DIARRHEA

Abstract: The gastrointestinal and antibacterial properties of dichloromethane: Methanol extract (DVE) and fractions (DVHF, DVDF and DVMF) from Desmodium velutinum Willd. DC. (Fabaceae) leaves were investigated. The extract and fractions significantly (p<0.05) reduced normal defecation in rats (33-100%) and significantly (p<0.05-0.001) protected rats against castor oil-induced diarrhea (40-100%). They significantly (p<0.05) prolonged the intestinal transit time of charcoal meal in mice and inhibited the spontaneous cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…where the result of LD50 was greater than 3000 mg/kg showing that D. velutinum extract is relatively safe for human consumption. This is however contrary to the reports of [15,16] where the oral administration of methanol extract of Desmodium velutinum leaves produced no physical signs of toxicity such as weakness, writhing, gasping, palpitation, anorexia, reduction in body weight, decreased respiratory rate or death up to the highest administered oral dose (5000 mg/kg body weight) within 24 h of post: administration. The oral LD 50 of DVE in mice was thus established to be greater than 5000 mg/kg.…”
Section: Discussioncontrasting
confidence: 97%
“…where the result of LD50 was greater than 3000 mg/kg showing that D. velutinum extract is relatively safe for human consumption. This is however contrary to the reports of [15,16] where the oral administration of methanol extract of Desmodium velutinum leaves produced no physical signs of toxicity such as weakness, writhing, gasping, palpitation, anorexia, reduction in body weight, decreased respiratory rate or death up to the highest administered oral dose (5000 mg/kg body weight) within 24 h of post: administration. The oral LD 50 of DVE in mice was thus established to be greater than 5000 mg/kg.…”
Section: Discussioncontrasting
confidence: 97%
“…It was found that administration of the methanol leaves extract of Desmodium velutinum alone resulted in approximately 72% inhibition of ulceration and this finding is in agreement with a similar study that reported the gastroprotective effect of leaves to extract of Desmodium velutinum against an ethanol-induced ulcer in experimental rats [25]. However, in this study, the concept of combination therapy of natural flora is introduced for the treatment of peptic ulcers which is evidently reported by [11,33] to be an effective treatment strategy.…”
Section: Discussionsupporting
confidence: 90%
“…Although it has been reported that dose-dependent crude leaves extract of Desmodium velutinum showed gastro protection against experimentally induced ulcers in Wistar rats using ethanol [25], this is the first report on the gastroprotective effects of a combination of crude methanol leaf extract of Desmodium velutinum and honey on ethanolinduced gastric ulcer in albino rat models. This study evaluated the acute toxicity, gastrotherapeutic and gastroprotective effect of crude methanol leaf extract of Desmodium velutinum combined with honey in rats.…”
Section: Introductionmentioning
confidence: 75%
“…Flavonoids such as quercetin have been reported to possess laxative effect by promoting gastrointestinal motility and mucinsecretion. 21 Flavonoids are hydroxylated phenolic substances known for several medicinal importance such as antioxidant, antiulcer, among others. [22][23][24] Tannins are astringent bitter compound found in a variety of plant that binds and precipitate proteins and other organic compounds including amino acids and alkaloids.…”
Section: Phytochemical Evaluation Of the Plant Fractionmentioning
confidence: 99%